Enhancing Economic Development Through Integrated Public Services: A Case Study in North Bengkulu Regency - Aprianty, Henny; Azwardi, Evy; Dani, Rahiman (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to explore the challenges faced by small businesses in utilizing the North Bengkulu Regency Integrated Service Office (KPT) for business licensing. The research seeks to identify the barriers preventing small business owners from participating in the licensing program. Methodology: A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The study involved small business owners, community members, and KPT officers to understand the issues related to the licensing process. Results: The study identified several key obstacles to small business participation in the KPT licensing program: High costs; Lack of awareness; Inadequate socialization; and Operational inefficiencies at KPT Additionally, limited capital, insufficient human resources, and perceptions of outdated licensing practices further contribute to low participation. Findings: The findings highlight the need for policy reforms in public service delivery, as well as increased efforts in socializing the licensing program to improve access for small businesses. These issues prevent small businesses from fully benefiting from the integrated licensing services. Novelty: This study provides new insights into the challenges small businesses face in accessing integrated licensing services, offering suggestions for improving public service delivery and supporting local economic growth. Originality: The originality of this study lies in its localized analysis of small business licensing challenges in North Bengkulu Regency, focusing on the barriers unique to this region and offering practical recommendations for improvement. Conclusions: To improve small business participation in the licensing program, reforms are needed in policy, socialization, and efficiency. Addressing these barriers will enable small businesses to contribute more effectively to local economic development. Type of Paper: Descriptive qualitative research.